Successful Ovarian Vein Embolization of a Multiparous Woman with Pelvic Congestion Syndrome - Setiani, Rissa U.; Batubara, Edwin A. D.; Adiarto, Suko; Siddiq, Taofan; Indriani, Suci; Siahaan, Irwan H. (International Journal of Angiology, 2021)
Pelvic congestion syndrome (PCS) is a clinical syndrome supported by specific findings, such as ovarian vein's dilatation, that cause pelvic vein congestion. Although many theories are explaining the pathophysiologies of this condition, the underlying cause remains unknown. The clinical manifestations of PCS are various including chronic pelvic pain (CPP), voiding disturbances, or ureteral obstruction. Imaging modality, such as ultrasonography, computed tomography (CT scan), magnetic resonance imaging (MRI), and venography, are needed to confirm and exclude the differential diagnosis. Currently, American venous forum guidelines recommended endovascular therapy which is percutaneous embolization as the first option therapy of PCS. Here, we reported a 35-year-old woman with PCS who underwent successful percutaneous embolization therapy.
Keywords: pelvic congestion syndrome; chronic pelvic pain; multiparous woman; venography; percutaneous embolization